International Public Sector Accounting Standards (IPSAS) Implementation and Financial Reporting: Issues and Challenges in South-East Nigeria - Sunny Biobele Beredugo (Journal of Accounting and Taxation, 2021)
The main objective of the study was to identify the challenges of IPSAS implementation in the Nigerian Public Sector. This was as a result of low level of accountability and improper application of accounting standards by government institutions. A structured questionnaire was used to elicit information from the various respondents. The population of the study consists of accountants, auditors and cash officers in government ministries, departments and agencies in Abia, Anambra, Enugu, Ebonyi and Imo States. The population was estimated at 8901for the five States. The sample size of 387 was drawn using the stratified sampling technique. The Analysis of Variance (ANOVA) was used for the hypothesis test. The results showed that the challenges that impinge the full implementation of IPSAS in Nigeria include: governments’ unwillingness in terms of political-will towards full IPSAS implementation; statutory adjustment, inadequate funding and institutional commitment among others. It was therefore recommended that there should be adequate funding for the IPSAS implementation projects as most of the Public Sector Entities attributed inability to implement IPSAS Accrual to paucity of funds. Government should also show more political will as well as commitment and support for the accrual basis IPSAS implementation at the Local Government level.